Stock Price Clustering and Discreteness - Harris, Lawrence (Review of Financial Studies, 1991)
Stock prices cluster on round fractions. Clustering increases with price level and volatility, and decreases with capitalization and transaction frequency. Clustering is pervasive. Price clustering will occur if traders use discrete price sets to simplify their negotiations. Exchange regulations require that most stocks be traded on eighths. Clustering on larger fractions will occur if traders choose to use discrete price sets based on quarters, halves, or whole numbers. An econometric model of clustering is derived and estimated. Projections from the results suggest that traders would frequently use odd sixteenths when trading low-price stocks, if exchange regulations permitted trading on sixteenths. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.